Design and Simulation of Disc-type Magnetorheological Brake based on Rectangular Bump - Weicheng Wang; Yiping Luo; Lei Wang; Hao Xiong (Jixie chuandong, 2021)
Based on the rheological properties of MRF，a disc-type MR brake with rectangular bump is designed，and the calculation formula of its braking torque is derived. The simulation model is established based on Matlab/Simulink， and the size parameters of rectangular bump are continuously optimized. The simulation results show that when there are 12 rectangular bumps with a width of 2 mm and a depth of 1.5 mm， the braking torque is 626 N·m， which is 31.5% higher than that of the bumps without machining. It shows that the designed MR brake can effectively improve the braking torque.